Hamilton the energetic founder - Bernstein, Richard B. 1956- (Oxford University Press, 2023)
"In Hamilton: The Energetic Founder, R. B. Bernstein provides a thorough history that reveals Hamilton's status as one of the key founding fathers of the United States.Hamilton: The Energetic Founder is a brief introduction to the life, thought, work, and legacy of Alexander Hamilton (1755-1804), but it is not a traditional biography. Public curiosity about Hamilton, his life, and his work has swelled, particularly among those intrigued by popular-culture portrayals in the Broadway musical Hamilton: An American Musical. This book presents a summary of Hamilton's life and explores his role in revolution, constitutionalism, economics, diplomacy, and war, as well as his relationship to honor culture and duelling. The epilogue considers Hamilton's legacies.The book considers Hamilton as a key founding father, focusing on his work as a politician, a constitutional thinker, and the nation's first secretary of the treasury."